1993
DOI: 10.1017/s0022215100124806
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of a complete response to and adverse effects of a CDDP-5FU combination as primary therapy for head and neck aquamous carcinomas

Abstract: Retrospective analysis of detailed patient and tumour factors associated with a complete response to combination inductive chemotherapy with CDDP-5FU (96 or 120 hour continuous infusion) was performed using data from 147 patients with a previously untreated squamous cell carcinoma of the oral cavity, oropharynx or pharyngo-larynx following completion of two (29 patients) or three (118 patients) cycles. Adverse reactions to chemotherapy were documented for all 164 patients included in the study. Eight drug-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Cognetti et al [34] reported that clinical stage was predictive for overall response while T status was significant specifically for CR. T stage, N stage and performance status have been also identified by others as important prognostic factors for CR to chemotherapy [35][36][37].…”
Section: Discussionmentioning
confidence: 90%
“…Cognetti et al [34] reported that clinical stage was predictive for overall response while T status was significant specifically for CR. T stage, N stage and performance status have been also identified by others as important prognostic factors for CR to chemotherapy [35][36][37].…”
Section: Discussionmentioning
confidence: 90%
“…A total of 146 studies were ultimately included in our meta‐analysis 9,24–167 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy in patients with various types of cancers, such as HNC and breast cancer, has been associated with a heightened risk of thromboembolic events. There have also been reports of ischemic cerebrovascular accidents occurring as a consequence of chemotherapy in these patient groups [10,14,31,32]. Various factors have been proposed as contributors to thromboembolism, including tumor embolization, vasculitis, nonbacterial thrombotic endocarditis, coagulopathy due to consumption, and adverse effects associated with chemotherapy drugs [33][34][35].…”
Section: Discussionmentioning
confidence: 99%